Pembelajaran Blended Learning Berbasis Rotation Model terhadap Kemampuan Berpikir Kritis Matematis Siswa - Ulya Ulfiyati; Himmatul Ulya (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
Fun and non-monotonous learning, as well as the COVID-19 pandemic, make teachers /lecturers think about learning that can solve the problem. Mathematics learning using a blended learning model based on rotation model is an implication of technological development, and is expected to provide solutions to the above problems. Mixing learning between conventional or face-to-face learning and online learning is expected to improve students' critical thinking skills.